The Influence of Wool Pellet Application on Alleviating Salt-Induced Stress in Soybean (Glycine max L.) - Lütfi Nohutçu (Life)
Soil salinity is a pervasive challenge in agricultural regions, significantly impacting plant growth and productivity. Addressing the adverse implications of soil salinization and capitalizing on organic waste resources has the potential to yield substantial advancements in the agricultural sector. This study examined the influence of varying levels of wool pellets (0, 1%, 2%, and 4%) and salt (0, 25, 50, and 100 mM) on the physiological and biochemical properties of soybean (Glycine max L.). The findings revealed that compared to the control group, at a 4% application rate, plant length decreased by 20%, while stem dry weight, root length and weight showed no significant differences up to a 2% application. Compared to the control treatment, the 4% application rate resulted in an increase of 6% in leaf temperature, 55% in NBI, 12% in chlorophyll content, and 10% in MDA activity. Conversely, the TAA, TPC, and carotenoid content decreased by 55%, 51%, and 81%, respectively. Salt applications led to reductions in most studied morphological parameters, except for root properties. Compared to the control, plant length, stem fresh weight, and stem dry weight decreased by 14%, 22%, and 14%, respectively, while root length, root fresh weight, and root dry weight increased by 18%, 33%, and 50%, respectively.